Duplex stainless steel of type UNS S32101 and ferritic stainless steel of type AISI 430 subjected to cathodic hydrogenation (International Journal of Scientific Research and Management (IJSRM), 2020)
This work presents a study on the duplex stainless steel UNS S32101 and ferritic AISI 430 when subjected to cathodic hydrogenation, to ascertain their behavior under the action of hydrogen. Throughout the research, with the aid of optical (MO), scanning electronics (SEM) and atomic force (AFM) microscopy, both hydrogen embrittlement and pitting corrosion after hydrogenation and degassing in UNS S32101 duplex stainless steel became evident. Subsequently, the X-ray diffraction performed to verify the phase transformations confirmed the transformation of the austenitic phase into the martensitic phase in the duplex steel and confirmed the formation of Cr23C6 precipitates in the ferritic steel. And so, it corroborated with the SEM images, proving the transformation of σ-phase agent of pitting corrosion in duplex steel.